KAJIAN PENAMBAHAN BUBUR KULIT BUAH NAGA MERAH (Hylocereus polyrhizus), TEPUNG MOCAF DAN TEPUNG TEMPE DALAM PEMBUATAN KUKIS - ', Indrianto '; Herawati, Netti '; ', Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to obtain powder formulations mocaf flour and pureed red dragon fruit leather best on the nutritional value of cookie-generated and with the SNI 01-2973-1992. This study uses a completely randomized design (CRD) with four treatments and four replications. The treatment in this study is K1 (mocaf flour 30%, pureed fruit peel red dragon 5%), K2 (mocaf flour 25%, pulp skin red dragon fruit 10%), K3 (mocaf flour 20%, pulp skin red dragon fruit 15 %) and K4 (mocaf flour 15%, red dragon fruit peel pulp 20%). The results showed that the treatment provides significant effect on moisture content, ash content, protein content, sensory assessment by descriptive and hedonic. Cookie-best treatment in this study is K2 with a water content of 4.32%, ash content of 1.98%, 9.56% protein content and the antioxidant content of 9.56%. Keywords: Red Dragon Fruit skin, Mocaf , Tempeh Flour, cookies